Influence of Civil Society through Grassroots Environmental Movement in Bangladesh - Labonno Saha; Farhat Tasnim (Khazanah Sosial, 2025)
Bangladesh is one of the most vulnerable countries due to climate change, its geographic location and socio-economic conditions. Civil society in Bangladesh has played a significant role in the environmental movement, driving both grassroots activism and influencing national policies related to environmental protection. The prime objective of this study is to explore the influence of civil society in the grassroots environmental movement, by examining the NGOs self-evaluation. The study employed a descriptive qualitative research approach to meet its objectives. Data was collected from 25 NGOs based on specific inclusion criteria. A semi-structured questionnaire is used to conduct interviews with selected respondents. NGOs overall influence is measured based on selected indicators, where five points Likert scale is used how much they are able to influence in grassroots environmental movement. Indicators like, Introduce environmental issues, youth leader creation, providing volunteers and trainers are scored high. On the other hand, political socialization, new organization creation, influence as pressure group are scored low based on NGOs self-evaluation. The study concluded by finding the obstacle of effective grassroots influence and making some proposals that CSOs, policymakers, and all stakeholders could consider while developing strategies for more influential civil society in Bangladesh.